Understanding Impeding Contexts to Implementation of the Abuja Declaration: Factors Associated with None Use of Treated Bed Nets among Pregnant Women in Tanzania (Tanzania Medical Journal, 2025)
BackgroundMalaria remains a significant public health problem despite ongoing efforts that began with Abuja Declaration on Roll Back Malaria (RBM) then Global Technical Strategy for Malaria 2016-2030 including RBM Partnership Strategic Plan 2018–2020. The Abuja Declaration's goal was to ensure that by 2005, 60% of pregnant women and children slept under a treated bed net (ITN), consequently reducing the burden of malaria by half. Ten years after Abuja Declaration Analysis of the Tanzania Demographic Health Survey and Malaria Indicator Survey (TDHMIS) 2015-2016 data that succeeded the Abuja Declaration target was done to shed light on factors to be addressed to bridge the gap to the target thus informing ongoing Malaria control strategies. MethodologyIt included extraction, cleaning and analysis of data for 1137 pregnant women that included bivariate analysis of the association of ITN and independent variables using STATA 12. Variables with p-value <0.02 were include in multivariate log-binomial regression model to determine independent variables, the significance level was p-value = 0.05.ResultsThe study included 1137 pregnant women of whom 55.7% slept under an ITN the previous night. Those with high likelihood of sleeping under an ITN were women from the richest wealth quintile compared with poorest; AOR=2.24395% CI (1.523-3.305); also having three or more under-five children AOR=2.9095%CI (1.511-5.57) and coming from house hold having a radio AOR=1.42 95%CI (1.05-1.91). Low likelihood was observed among those without health insurance AOR 0.44, 95CI (0.24-0.78) and coming from household without electricity AOR=0.36, 95%CI (0.14-0.94), these were significantly associated with pregnant women sleeping under a treated bed net last night.Conclusion and recommendationsAbuja declaration gap to target was significant despite the ongoing efforts, since only 55.5% pregnant women utilized ITNs compared to 2005 Abuja 60% target and hence it has been off-track for the ten years. Factors associated were wealth, fewer children in a household, electrified households, radios possession and health insurance enrolment. Thus, it is recommended to merge strategies on access to media, knowledge empowerment and poverty alleviations along with sustained access to treated bed nets to be on track with the rollback malaria strategies.